All about flooble | fun stuff | Get a free chatterbox | Free JavaScript | Avatars    
perplexus dot info

Home > Just Math
Is It Necessary and Sufficient (Posted on 2008-02-27) Difficulty: 2 of 5
Let a,b,c be real numbers. Is a,b,c≥0 the necessary and sufficient condition to show that a3+b3+c3≥3abc? If not, find the condition that is both sufficient and necessary.

See The Solution Submitted by Praneeth    
Rating: 3.5000 (2 votes)

Comments: ( Back to comment list | You must be logged in to post comments.)
Solution Puzzle Solution | Comment 3 of 5 |

Since each of a, b and c are real, it follows that:
(a-b)^2 > = 0, (b-c)^2 > = 0 and (c-a)^2 > = 0, so that:
(a^2+b^2+c^2 –ab-bc-ca)
= 1/2*{(a-b)^2 + (b-c)^2 + (c-a)^2)
> = 0

Now, we know that:

a^3+b^3+c^3 – 3*a*b*c = (a+b+c) (a^2+b^2+c^2 –ab-bc-ca) ……(*)

Now, a^2+b^2+c^2 –ab-bc-ca> = 0. Thus, if a+b+c >= 0, then it follows that the lhs of (*) is > = 0

If lhs of (*) > 0, then (a^2+b^2+c^2 –ab-bc-ca)  cannot be 0, since that would force a^3+b^3+c^3 – 3*a*b*c = 0, a contradiction.
Hence, (a^2+b^2+c^2 –ab-bc-ca)> 0 in terms of (i), so that a+b+c > 0

If lhs of (*) is 0, then:
Either, a+b+c = 0
Or, a^2+b^2+c^2 –ab-bc-ca= 0
-> 1/2*{(a-b)^2 + (b-c)^2 + (c-a)^2) = 0.
-> (a-b)^2 + (b-c)^2 + (c-a)^2 = 0

Since each of a, b and c are real, it follows that each of (a-b)^2, (b-c)^2 and (c-a)^2 must be equal to 0
Accordingly, a=b=c

Consequently, the condition that is both sufficient and necessary would be:

a+b+c >=0, OR a=b=c

Edited on February 28, 2008, 5:19 am
  Posted by K Sengupta on 2008-02-27 23:57:58

Please log in:
Login:
Password:
Remember me:
Sign up! | Forgot password


Search:
Search body:
Forums (0)
Newest Problems
Random Problem
FAQ | About This Site
Site Statistics
New Comments (9)
Unsolved Problems
Top Rated Problems
This month's top
Most Commented On

Chatterbox:
Copyright © 2002 - 2017 by Animus Pactum Consulting. All rights reserved. Privacy Information